THE INFLUENCE OF FASHION INNOVATIVENESS ON BEHAVIORAL INTENTION MEDIATED BY BRAND IMAGE AND BRAND LOVE - Miwa, Nina Deskartika; Hussein, Ananda Sabil; Rahayu, Mintarti (Jurnal Aplikasi Manajemen, 2023)
The study aimed to investigate the impact of fashion innovation, brand image, brand love, and behavioral intention on Customers of Ria Miranda products in Malang. The research sample consisted of 200 purposively selected Customers of Ria Miranda products, with the data being analyzed using the partial least squares (PLS) methodology through SmartPLS. The research methodology involved an assessment of the internal consistency of the measurement models, the examination of outer models, the construction of path diagrams, and the testing of hypotheses. The study's findings suggest that fashion innovation directly impacts customer behavioral intention toward Ria Miranda products. Additionally, brand image and love mediate between fashion innovation and customer behavioral intention towards Ria Miranda products. To conclude, the study demonstrated the significant impact of fashion innovation on customer behavioral intention towards Ria Miranda products and the mediating role of brand image and brand love in this relationship. The high satisfaction level of these customers results in strong brand loyalty, further strengthened by brand love. The findings of this study indicate that customer behavioral intention can be formed if the fashion product management focuses on exploring the existing advantages of the brand, such as the dimension of fashion innovativeness while considering the brand image and the emotional feelings of the customer. When processed, a high-quality brand image and the emotional feelings of the customer play a full role as mediators in affecting behavioral intention.